Pekarangan Model for Supporting Food Resiliency on Household Level in Transmigration Area, East Lampung - Ali, Muhammad Saddam; Arifin, Hadi Susilo; Arifin, Nurhayati; Astawan, Made (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2022)
Pekarangan as one of the potential natural resources and closest to the family can be the right and strategic choice to be used in realizing family-scale food resiliency. The research was conducted in Transmigration area of ​​East Lampung from June 2021 to December 2021. The determination of the pekarangan sample by purposive sampling was carried out on four transmigration ethnics, i.e., the Javanese (100 samples), the Sundanese (100 samples), the Balinese (100 samples) , and the Madurese (13 population), as well as local transmigration, i.e., the Lampungnese (100 samples). Pekarangan model is determined from species diversities on agroforestry system and its plant multistorey condition. The results of identification found three agroforestry systems as a pekarangan model, i.e., the agroforest system (Maduranese pekarangan), agrosilvopastoral (Balinese, Javanese, and Lampungnese pekarangans), and agrosilvopastoralfishery (Sundanese pekarangan). Each agroforestry system contributed to food sources by 54.54% (agroforest), 46.15% to 65.51% (agrosilvopastoral), and 89.28% (agrosilvopastoralfishery).